User-Friendly Website Design: A Combined Eye-Tracking Study - Julia Lamberz; Thorsten Litfin; Gunther Meeh-Bunse; Teckert Özlem (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
A simple and intuitive operation – the so-called usability analysis of websites – is indispensable in modern times. In particular, drop-out rates can be applied as an indicator of existing usability problems. Eye-tracking is a proven method for the evaluation of the usability of websites. The aim of the study was to improve the usability of the website of an educational institute for trainees in the region as the target group. For this purpose, the use of an eye-tracking technology was combined with a survey of 30 trainees. The eye-tracking study was task-oriented: subjects were asked to inform themselves of particular course offers, and to register for the relevant courses. This procedure and the subsequent survey provided tangible indications of the search and surfing behaviour of the target group as well as their assessment of the usability of the website. This combination of methods allows the development of recommendations for optimizing the website with regard to its orientation, structure and level of comprehensibility.
Keywords: M15; M31; 330; eye-tracking; usability evaluation; website usability